Pengaruh CR, DER dan DPR Terhadap Pertumbuhan Laba Perusahaan Sektor Consumer Non-Cyclicals - Ferencia Trinita Simanjuntak; Faradila Meirisa (MDP Student Conference, 2026)
This study aims to analyze the effect of CR, DER, and DPR on the profit growth of companies in the non-cyclical consumer sector. This study uses a quantitative method. Over a period of five years, 29 samples were collected using purposive sampling. Data analysis was performed using multiple linear regression. The conclusion of this study reveals that CR and DPR have an effect on profit growth, but DER does not have an effect on profit growth.